HIV status does not have an impact on positron emission tomography-computed tomography (PET-CT) findings or radiotherapy treatment recommendations in patients with locally advanced cervical cancer. Issue 8 (13th August 2019) - Simonds, Hannah; Botha, Matthys Hendrik; Ellmann, Annare; Warwick, James; Doruyter, Alex; Neugut, Alfred I; Van Der Merwe, Haynes; Jacobson, Judith S
Abstract : Introduction: Positron emission tomography-computed tomography (PET-CT) imaging is commonly used to identify nodal involvement in locally advanced cervical carcinoma, but its appropriateness for that purpose among HIV-positive patients has rarely been studied. We analyzed PET-CT findings and subsequent treatment prescribed in patients with locally advanced cervical carcinoma in Cape Town, South Africa. Methods: We identified a cohort of consecutive cervical carcinoma patients International Federation of Gynecology and Obstetrics (FIGO) stage IIB to IIIB at our cancer center who underwent a planning 18-fluorodeoxyglucose ( 18 FDG) PET-CT scan from January 2015 through December 2018. Demographics, PET-CT findings, and subsequent treatment prescribed were recorded. Patients were selected for PET-CT only if they had no signs of distant disease on staging chest X-ray or abdominal ultrasound; were deemed suitable for radical chemoradiation by the multi-disciplinary team; and had normal renal function. HIV-positive patients ideally had to have been established on continuous antiviral therapy for more than 3 months and to have a CD4 cell count above 150 cells/μL. Small cell and neuroendocrine carcinoma cases were excluded from the study. Differences in demographic and clinical measures between HIV-positive and HIV-negative patients were evaluated by means of t-tests for continuous variables and χ 2 tests for categorical variables. Results: Over a 4 year period, 278 patients—192 HIV-negative (69.1%) and 86 HIV-positive (30.9%)—met the inclusion criteria. HIV-positive patients had a median CD4 count of 475 cells/µL (IQR 307–612 cells/µL). More than 80% of patients had pelvic nodal involvement, and more than 40% had uptake in common iliac and/or para-aortic nodes. Nodal involvement was not associated with HIV status. Fifty-four patients (19.4%) had at least one site of distant metastatic disease. Overall, 235 patients (84.5%) were upstaged following PET-CT staging scan. Upstaging was not associated with HIV status (HIV-negative 83.9% vs HIV-positive 87.2%; p=0.47). Ten patients who did not return for radiotherapy were excluded from the analysis. Following their PET-CT scan, treatment intent changed for 124 patients (46.3%): 53.6% of HIV-positive patients and 42.9% of HIV-negative patients (p=0.11). Conclusion: We found no differences between HIV-positive or HIV-negative patients in nodal involvement or occult metastases, and PET-CT imaging did not lead to, or justify, treatment differences between the two groups. Future studies will evaluate survival and correlation of upstaging with outcome.